The Mechanism of Variegation in immutans Provides Insight into Chloroplast Biogenesis - Foudree, Andrew; Putarjunan, Aarthi; Kambakam, Sekhar; Nolan, Trevor; Fussell, Jenna; Pogorelko, Gennady; Rodermel, Steven (Frontiers in Plant Science, 2012)
Abstract: The immutans (im) variegation mutant of Arabidopsis has green and white-sectored leaves due to the absence of fully functional PTOX (plastid terminal oxidase), a plastoquinol oxidase in thylakoid membranes. PTOX appears to be at the nexus of a growing number of biochemical pathways in the plastid, including carotenoid biosynthesis, PSI cyclic electron flow, and chlororespiration. During the early steps of chloroplast biogenesis, PTOX serves as an alternate electron sink and is a prime determinant of the redox poise of the developing photosynthetic apparatus. Whereas a lack of PTOX causes the formation of photooxidized plastids in the white sectors of im, compensating mechanisms allow the green sectors to escape the effects of the mutation. This manuscript provides an update on PTOX, the mechanism of immutans variegation, and findings about im compensatory mechanisms.